APPLICATION OF EHEALTH FOR PATIENT AWARENESS DURING DISASTER FANI: A GOVT. INITIATIVE - Kar, Dr. Leena (International Journal of Psychosocial Rehabilitation, 2020)
Use of electronic media in ehealth technology for RCH patient awareness for their treatment to be done institutionalized during disaster play a significant role in terms of responsible and ethical coverage. The Govt. use TV and social media which as information broker and conduit of information in the affected region during the response and recovery phase. The govt. are expected to give accurate, professional, comprehensive and timely data when there are injuries, fatalities and RCH interventions are involved. The health management information system can also be used for outreach the probable RCH patients to provide them shelter,to provide them shelter, to provide them education regarding treatment and facility available in healthcare system, to reduce their stress and panic level. Here the author describes Ray Jone’s Conceptual map and Lily model to propose her own conceptual model and relates different literature for disaster technology response and assess the RCH patient awareness and satisfaction level during their stay at Hospital during disaster Fani because of ehealth technology improving efficiency healthcare system.